Thermal and Cardiovascular Strain Mitigate the Potential Benefit of Carbohydrate Mouth Rinse During Self-Paced Exercise in the Heat - Cramer, Matthew N.; Thompson, Martin W.; Périard, Julien D. (Frontiers in Physiology, 2015)
Purpose: To determine whether a carbohydrate mouth rinse can alter self-paced exercise performance independently of a high degree of thermal and cardiovascular strain. Methods: Eight endurance-trained males performed two 40-km cycling time trials in 35°C, 60% RH while swilling a 20-ml bolus of 6.5% maltodextrin (CHO) or a colour- and taste-matched placebo (PLA) every 5 km. Heart rate, power output, rectal temperature (Tre), and mean skin temperature (Tsk) were recorded continuously; cardiac output, oxygen uptake (VO2), mean arterial pressure (MAP), and perceived exertion (RPE) were measured every 10 min. Results: Performance time and mean power output were similar between treatments, averaging 63.9 ± 3.2 and 64.3 ± 2.8 min, and 251 ± 23 and 242 ± 18 W in CHO and PLA, respectively. Power output, stroke volume, cardiac output, MAP, and VO2 decreased during both trials, increasing slightly or remaining stable during a final 2-km end-spurt. Tre, Tsk, heart rate, and RPE increased throughout exercise similarly with both treatments. Changes in RPE correlated with those in Tre (P<0.005) and heart rate (P<0.001). Conclusions: These findings suggest that carbohydrate mouth rinsing does not improve ~1-h time trial performance in hot-humid conditions, possibly due to a failure in down-regulating RPE, which may be influenced more by severe thermal and cardiovascular strain.